Production of the First Effective Hyperimmune Equine Serum Antivenom against Africanized Bees - Santos, Keity Souza; Stephano, Marco Antonio; Marcelino, Jose Roberto; Resende Ferreira, Virginia Maria; Rocha, Thalita; Caricati, Celso; Higashi, Hisako Gondo; Moro, Ana Maria; Kalil, Jorge Elias; Malaspina, Osmar [UNESP]; Morato Castro, Fabio Fernandes; Palma, Mario Sergio [UNESP] (Public Library Science, 2013)
Victims of massive bee attacks become extremely ill, presenting symptoms ranging from dizziness and headache to acute renal failure and multiple organ failure that can lead to death. Previous attempts to develop specific antivenom to treat these victims have been unsuccessful. We herein report a F(ab)'(2)-based antivenom raised in horse as a potential new treatment for victims of multiple bee stings. The final product contains high specific IgG titers and is effective in neutralizing toxic effects, such as hemolysis, cytotoxicity and myotoxicity. The assessment of neutralization was revised and hemolysis, the primary toxic effect of these stings, was fully neutralized in vivo for the first time.